Assessing ESL undergraduate performance in a group oral test: Rater orientations - Sim, Tam Shu; Don, Zuraidah Mohd; Kuan, Chue Siu (Indonesian Journal of Applied Linguistics, 2019)
Group oral testing has attracted increasing interests in performance-based assessment, mainly due to its ability to measure interactional competence. Increasing attention has consequently been paid to the performance of raters, whose orientations have an impact on the scores in view of their role as mediators between performances and scores. Studies have shown that despite training, raters’ personal constructs can lead to different assessments. This study examines rater orientations before and after viewing student performance in an oral test, to discover whether raters subscribe to the view that interaction is individual-focused and is mainly a representation of cognitive or within-language user construct, or whether they believe in a social perspective of interaction. Fourteen participants were interviewed to ascertain their personal constructs for assessing group oral interaction, as well as their justifications for rating a videotaped group oral performance using these personal constructs. The findings show that while raters valued a number of qualities including linguistic abilities, their focus was on interaction. This suggests an inclination towards the social interactional perspective, as they seem well aware that successful interaction is co-constructed, and cannot be achieved through individual language ability alone.